Study and analysis factor that can improve the fringing electric field (FEF) soil moisture sensor for agriculture applications: article / Wan Azlan Hasan - Hasan, Wan Azlan (2013)
This project aims to study on the effect of the dimension and the width of sense and drive electrode to the sensitivity of the fringing electric filed (FEF) sensors. Fringing electric filed (FEF) sensor has been used for non-invasive measurement of material of properties such as temperature and hardness. FEF also been used to detect existence or concentration of material within the test environment. Using the FEF application the FEF moisture sensor is made to detect the volumetric water content (VWC) in soil. In this study, the simulation and testing has been done to characterize the sensor. The simulation is using Finite Element Method Magnetic (FEMM) while sensor is tests using LCR meter to get capacitance value. Through capacitance value the volumetric water content (VWC) can be measured. Before testing is conducted the sensor needs to fabricate using Printed Circuit Board (PCB). The result between simulation and testing then been compare. The results show the electrode width effect the sensor sensitivity. The sensor sensitivity is high when the electrode width is small.